IMPROVING THE ORGANIZATIONAL-ECONOMIC MECHANISM FOR ENSURING SUSTAINABLE AGRICULTURAL DEVELOPMENT - Ergashev, Gayrat Urolovich (THE INNOVATION ECONOMY, 2026)
This article presents a comprehensive approach to improving the organizational and economic mechanism for ensuring sustainable development of agriculture in Uzbekistan. Based on official data from the State Statistics Committee of the Republic of Uzbekistan, the Food and Agriculture Organization (FAO), the World Bank, and the Ministry of Agriculture of Uzbekistan for the period 2018–2023, resource efficiency, as well as the state of institutional and financial mechanisms in the agricultural sector, were quantitatively assessed. The research findings indicate that institutional fragmentation, insufficient financial support, and the low level of digital technology adoption are the key factors reducing the effectiveness of the existing organizational and economic mechanism. The article proposes an integrated model of an organizational and economic mechanism for ensuring sustainable development, along with pathways for its regional implementation.